Start-up of full-scale two-stage upflow anaerobic sludge blanket (UASB) reactors treating distillery slops - Ghimire, Ashok B. (1999)
This study is an evaluation of the start-up performance of full-scale tow-stage upflow anaerobic sludge blanket (UASB) reactors, treating distillery slops of an alcohol distillery in the Philippines. Each stage consisted of three reactors. These reactors were inoculated with non-granular seed sludge acquired from an existing methane upflow reactors (MURs), treating slops of the same distillery. The reactor pH was stable and within range, i.e., 6.8-7.5. The temperature of the reactors was within the desired operating range of 35-38°C (mesophilic). There were no observed reactor upsets which could be attributed to sudden increase in volatile fatty acids (VFA) levels in the reactor contents, indicating that the system had sufficienct buffering capacity. The methane content of biogas was 57-62%. The produced biogas was used to generate power for the plant operations. An upflow velocity increment of 0.4 m for every day resulted in sludge washout, especially in second-stage reactors. Nevertheless after the re-addition of more seed sludge and nuclei to the reactors, and adjusting the upflow velocity increase to 0.5m for every 2-4 days, the sludge production and its retention in the reactors significantly improved with time. Sludge concentration varied over depth. It was higher in the lower sections of the reactors. The smaller and poorly-settling sludge developed in the lower depths of the reactors. As a result, more sludge with better settleability accumulated in the reactors.